Evaluation of System Access Security in The Implementation of Multi-Factor Authentication (MFA) in Educational Institutions - Cahyaningrum, Yuniana (DPPM Universitas Pelita Bangsa, 2024)
Information systems in educational institutions have the potential to be targeted by various parties, especially unauthorized parties, so they require a higher layer of security to protect sensitive data and secure user access. One solution that can be implemented is the implementation of Multi-Factor Authentication (MFA), a security approach that utilizes more than one authentication method to secure access to the system. MFA is a security method that requires more than one way to verify a user's identity when accessing a system, application, or service that aims to increase security by adding an additional layer of protection beyond using a single passphrase or password. This research aims to evaluate the effectiveness and impact of implementing MFA in the context of system access security in educational environments. The research methodology involves surveying system users, statistical analysis, and monitoring access activity to assess the extent to which MFA is successful in reducing security risks and protecting sensitive information. The research results show that the use of MFA in educational institutions can significantly increase system access security. Several obstacles that arise become challenges in solving problems regarding the use of MFA. Therefore, this article also examines recommendations for increasing the implementation of MFA in educational institutions. It is hoped that this research can contribute to the positive impact of MFA in improving system access security in the context of educational institutions by optimizing information technology in protecting data integrity and user access security.